Pais e filhos: um estudo da educação financeira em famílias na fase de aquisição - Manfredini, Andreza Maria Neves (2007)
Living in a society where publicity constitutes a mass appeal for consumption, children soon are brought into contact with money; therefore, raising children financially constitutes a challenge for parents. This research aimed at understanding how the process of financial education of children occurs inside middle class families, during the Acquisition Phase of the Vital Cycle, in the city of Tremembe, State of Sao Paulo. This study characterized itself as a qualitative research, carried out among parents and children at the age of 7 to 10. In order to collect data, three focal groups were formed: the first one composed of 6 parents, of which 5 were mothers and 1 father who had children at the age of 7 to 10; the other group composed of 9 children at the age of 7 to 8; and the third one composed of 5 children at the age of 9 to 10. The participants constituted a snowball sampling. During the narrative analysis, it was verified that the parents do not have the intentionality of educating their children towards money itself, and for that reason they make use of techniques developed in everyday family life. The older children are able to recognize that the parents have more experience in dealing with money, and therefore, believe that it is important to talk about this topic. It is realized that the financial education model passed on to the parents is the same that they will try to pass on to their children. It is also realized that the action of saving should be made continuous and a priority, as well as family talks, in order that children are able to act as citizens and not only ordinary consumers, in the near future